2020
DOI: 10.1136/archdischild-2019-318594
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of outborn very-low-birth-weight infants in Japan

Abstract: BackgroundOutcomes of prenatal covariate-adjusted outborn very-low-birth-weight infants (VLBWIs) (≤1500 g) remain uncertain.ObjectiveTo compare morbidity and mortality between outborn and inborn VLBWIs.DesignObservational cohort study using inverse-probability-of-treatment weighting.SettingNeonatal Research Network of Japan.PatientsSingleton VLBWIs with no major anomalies admitted to a neonatal intensive care unit from 2012 to 2016.MethodsInverse-probability-of-treatment weighting with propensity scores was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 38 publications
2
29
0
2
Order By: Relevance
“…10 In a retrospective cohort study of preterm infants in Japan from 2003 to 2012, Nakanishi et al found that the mortality rate was 6.5%, 7 whereas from 2012 to 2016, Hirata et al reported a mortality rate of 4.1%. 8 Considering these data, the mortality rate in the present study seemed to be very low, especially in the extremely LBW group (5.2%). A study including a multicenter, multinational cohort of preterm infants among eight members of the International Network for Evaluating Outcomes spanning nine countries 11 —and more recently a study of neonatal outcomes in 11 high-income countries 12 —, found that mortality was lowest in Japan.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…10 In a retrospective cohort study of preterm infants in Japan from 2003 to 2012, Nakanishi et al found that the mortality rate was 6.5%, 7 whereas from 2012 to 2016, Hirata et al reported a mortality rate of 4.1%. 8 Considering these data, the mortality rate in the present study seemed to be very low, especially in the extremely LBW group (5.2%). A study including a multicenter, multinational cohort of preterm infants among eight members of the International Network for Evaluating Outcomes spanning nine countries 11 —and more recently a study of neonatal outcomes in 11 high-income countries 12 —, found that mortality was lowest in Japan.…”
Section: Discussionmentioning
confidence: 43%
“…6 In a retrospective cohort study of preterm infants treated from 2003 to 2012 in Japan, Nakanishi et al found that the rates of IVH were 14.1% from 2003 to 2007 and 14.0% from 2008 to 2012, whereas the equivalent figures for infants with severe IVH were 5.6 and 4.3%, respectively. 7 From the period of 2012 to 2016, Hirata et al 8 reported that the overall rate of severe IVH was 4.3%, whereas that of IVH of any grade was 13.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the rate of IVH stands at around 20–38% in children under 28 weeks of gestational age (GA) and is more frequent in the first 72 h of life [ 19 , 20 ]. Thus, the risk of bleeding is inversely related to gestational age and can be attributed to three factors: vascular immaturity of the germinal matrix, deficient extravascular matrix, and cerebral blood flow alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Centralisation of perinatal care in tertiary hospitals reduces their mortality and morbidity (1)(2)(3). Infants born outside a tertiary centre and who require transport after birth have an increased risk of intracranial haemorrhage (ICH), necrotising enterocolitis, spontaneous intestinal perforation and pulmonary haemorrhage (4)(5)(6)(7)(8)(9). In some populations, this has translated into long-term neurodevelopmental impairment (7,10,11).…”
mentioning
confidence: 99%